Development, physicochemical characterization, and antimicrobial evaluation of niosomal myrtle essential oil - Mahboobeh Raeiszadeh; Abbas Pardakhty; Fariba Sharififar; Alireza Farsinejad; Mehrnaz Mehrabani; Hossein Hosseini-nave; Mitra Mehrabani (Wolters Kluwer Medknow Publications, 2018)
Myrtus communis (myrtle) is well known for its therapeutic effects pertaining to the major secondary metabolites including essential oils (EOs). EOs are composed of volatile compounds and simply evaporate or decompose leading to their instability. Preparation of EOs niosomal formulation may be a promising approach to deal with these obstacles. Niosomal formulations of myrtle essential oil (nMEO) were provided using non-ionic surfactants and cholesterol (Chol). In the next steps, vesicle size, zeta potential, percentage of entrapment efficiency (EE%) and physical stability of nMEO were investigated. Finally, the effect of myrtle essential oil (MEO) and nMEO on microbial growth inhibition were assessed. Values for nMEO size and zeta potential ranged from 6.17 ± 0.32 to 7.24 ± 0.61 (μm) and -20.41 ± 0.17 to -31.75 ± 0.45 (mV), respectively. Higher degrees of EE% were obtained by F6 formulation (Span/Tween 60:Chol (50:50 molar ratio)). Moreover, niosomes have been reported to be stable at 4 °C during a three-month time period. It was revealed that nMEO F6 formulation inhibited growth of Staphylococcus aureus, Staphylococcus epidermidis, Serratia marcescens, and Bacillus subtilis at concentrations lower than that of MEO. Overall, it was found that stable multilamellar vesicles were formed in the presence of 0.5% MEO and F6 formulation. This formulation also exhibited better antibacterial activity than MEO.